#TITLE_ALTERNATIVE# - NUANSA AINI (NIM 10304005), CRYSTAL
Quasi Periodic Oscillation (QPO) in GX 5-1 was discovered by van der Klis (1985). LMXB has been divided into two sources, Z and Atoll sources, based on correlations between their spectral behaviour and timing properties at X-ray wavelenghts (Hasinger and van der Klis, 1989). Hasinger and van der Klis has analyzed 16 LMXB, using data from EXOSAT. In the colour-colour diagram, we can know that Z source usually form a Z shape, and may be divided into three branch. Those are Horizontal Branch (HB), Normal Branch (NB) dan Flaring Branch (FB). From the same plot of colour-colour diagrams, we have another sources. Because it is similar with Atoll, so these source gave name Atoll Source. Different from Z source, Atoll source just has two fragment like Island State and Banana State. Banana State has a Lower Banana and Upper Banana. Atoll sources did not show QPO phenomenon. Vrtilek (1990) has proved that in the Z sources, accretion rate increases monotically from HB to FB. Correlation between the observation of X-ray and UV revealed it. For Atoll source, accretion rate increases from Island State to Banana State (Gierlinski and Done, 2001), using three Atoll sources that Aql X-1, 4U1608-52 and 4U1705-44, from RXTE.